(untitled) (Scientific journal of the Fergana State University, 2023)
This article is dedicated to the national art of Macom and presents the theoretical and practical analyses of the structure, features of the melody and rhythm along with the text content of the Sarahbori Rost series from the vocal part of Rost in Shashmakom.